Epigenetic silencing in transgenic plants - Rajeev Kumar, Sarma; Anunanthini, Pushpanathan; Ramalingam, Sathishkumar (Frontiers in Plant Science, 2015)
Epigenetic silencing is a natural phenomenon in which the expression of gene is regulated through modifications of DNA, RNA or histone proteins. It is a mechanism for defending host genomes against the effects of transposable element, viral infection and acts as a modulator of expression of duplicated gene family members and as a silencer of transgenes. A major breakthrough in understanding the mechanism of epigenetic silencing was discovery of silencing in transgenic tobacco plants due to interaction between two homologous promoters. The molecular mechanism of epigenetic mechanism is highly complicated and it is not completely understood yet. Two different molecular routes have been proposed for this, i.e. transcriptional gene silencing (TGS), which is associated with heavy methylation of promoter regions and blocks the transcription of transgene. The basic mechanism underlying post-transcriptional gene silencing (PTGS) is degradation of the cytosolic mRNA of transgenes or endogenous genes. Undesired transgene silencing is of a major concern in transgenic technology used in crop improvement. A complete understanding of this phenomenon will be very useful for transgenic applications, where silencing of specific genes are required. The current status of epigenetic silencing in transgenic technology has been discussed and summarized in this mini-review.